Controlling factors of Ca isotope fractionation in scleractinian corals evaluated by temperature, pH and light controlled culture experiments. (15th October 2015) - Inoue, Mayuri; Gussone, Nikolaus; Koga, Yasuko; Iwase, Akihiro; Suzuki, Atsushi; Sakai, Kazuhiko; Kawahata, Hodaka
Abstract: In this study, the 44 Ca/ 40 Ca ratios of Porites australiensis grown under three different culture experiments composed of temperature, pH and light controlled culture experiments are measured. The temperature dependent isotope fractionation of 0.02‰/°C deduced from this study is similar to inorganic aragonite, but the degree of isotope fractionation is about +0.4‰ offset in corals. These observations agree with earlier results on different coral species, suggesting Ca isotope fractionation during Ca transmembrane transport in corals. While in cultured corals a significant temperature dependence of δ 44 Ca is observed, the relationships between calcium isotope fractionation and pH as well as light intensity are negligible. Therefore variation of δ 44 Ca in Porites corals is mainly controlled by temperature. A combination of δ 44 Ca and Sr/Ca of corals in temperature controlled experiments cannot be explained by Rayleigh type fractionation directly from a fluid, which is seawater-like in terms of δ 44 Ca and Sr/Ca. Through coral-specific biomineralization processes, overall mean δ 44 Ca of scleractinian corals including previous studies are different from biogenic aragonites secreted by sclerosponges and pteropods, but are comparable with those of bivalves as well as calcitic coccolithophores and foraminifers. These findings are important for better understanding biomineralization in corals and in order to constrain the Ca isotopic composition of oceanic Ca sinks in response to climate changes and associated with shifts of calcite and aragonite seas.